Questionable diagnostic benefit of the commercially available panel of bee venom components. Issue 9 (31st March 2017) - Arzt, L.; Bokanovic, D.; Schrautzer, C.; Schwarz, I.; Laipold, K.; Aberer, W.; Sturm, G. J.
Abstract: For many years, only the major allergen rApi m 1 has been available on the ImmunoCAP system for routine diagnosis of bee venom (BV) allergy. Now, there are five components available, and we aimed to detect the sensitivity and specificity of rApi m 1, 2, 3, 5, and 10 in BV‐allergic patients. We further evaluated the sensitivity of rApi m 1 and 2 of an alternative platform and investigated possible differences in the sensitization profile between monosensitization and clinically relevant double sensitization. Analysis of the whole panel of BV allergens of the CAP system still resulted in a lower sensitivity than analysis of the combination of rApi m 1 and 2 of the Immulite (71.6% vs 85.8%). Sensitization rate of rApi m 5 was more than doubled in double‐sensitized patients, while there was no difference for rApi m 2. The benefit of the commercially available panel of BV components is questionable, due to the insufficient sensitivity and still unavailable important cross‐reacting allergens.